Nutritional evaluation of Eysenhardtia polystachya (kidneywood) in Cuauhtémoc, Zacatecas, Mexico - Muñoz-Salas, Luis Cuauhtémoc; García-Cervantes, Daniel; Gutiérrez-Bañuelos, Héctor; Villarreal-Guerrero, Federico; Sánchez-Gutiérrez, Ricardo Alonso; Espinoza-Canales, Alejandro (Revista Mexicana de Ciencias Agrícolas, 2025)
Some legumes present in semi-arid regions are important because they can be used as forage in grasslands and have been studied as a food resource for ruminants. This study aimed to evaluate the nutritional quality of kidneywood in a semi-dry climate in Zacatecas, Mexico. Between 2021 and 2022, 20 random samplings were carried out in a 100 ha rangeland. The variables measured were ash (A), organic matter (OM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF) and in vitro degradability of dry matter (ivDDM). The highest amount of CP (p< 0.05) occurred in spring with 25.8%. The highest level of neutral detergent fiber was observed in the autumn and summer (59.17 and 56.26%) and the lowest in spring and winter (43.25 and 39.77%). The highest acid detergent fiber was obtained in summer (36.67%) and the lowest in winter (24.68%). In the and in vitro degradability of dry matter, no significant differences were found (p> 0.05), averaging 45.06%. The shrub provides the highest levels of protein in spring and adequate levels of fiber for use in ruminants.